Systematic Chemical Analysis Approach Reveals Superior Antioxidant Capacity via the Synergistic Effect of Flavonoid Compounds in Red Vegetative Tissues - Qin, Xiaoxiao; Lu, Yanfen; Peng, Zhen; Fan, Shuangxi; Yao, Yuncong (Frontiers in Chemistry, 2018)
The flavonoid system comprises an abundance of compounds with multiple functions; however, their potential synergism in antioxidant function remains unclear. We established an approach using ever-red (RL) and ever-green leaves (GL) of crabapple cultivars during their development to determine interrelationships among flavonoid compounds. RL scored significantly better than GL in terms of the type, composition, and diversity of flavonoids than GL. Principal component analysis predicted flavonoids in RL to have positive interaction effects, and the total antioxidant capacity was significantly higher than the sum of antioxidant capacities of the individual compounds. This synergy was verified by the high antioxidant capacity in rat serum after feeding on red leaves. Our findings suggest that the synergistic effect is a result of the high transcription levels regulated by McMYBs in RL. In summary, individual flavonoids cooperate in a flavonoid system, thus producing a synergistic antioxidant effect, and the approach used herein can provide insights into the roles of flavonoids and other compounds in future studies.